FGF21 and its Relationship with Inflammatory and Metabolic Parameters in HIV Patients after Antiretroviral Treatment - Ruiz-Padilla, Alan J.; Ruiz-Noa, Yeniley; del Rocio Ibarra-Reynoso, Lorena; Lazo-de-la-Vega-Monroy, Maria-Luisa; Alonso-Castro, Angel Josabad; Sánchez-Barajas, Mauricio; Alvarez-Alvarez, Rosa Margarita; del Carmen Preciado-Puga, Mónica (Current HIV Research, 2020)
Background: Fibroblast Growth Factor 21 (FGF21) serum levels are associated with insulin resistance and metabolic syndrome in HIV patients. Objective: To quantify FGF21 levels in HIV patients using antiretroviral therapy (ART) and to analyze a possible association between serum FGF21 levels and lipid profile, levels of proinflammatory cytokines, and atherogenic risk factors. Materials and Methods: Twenty patients with HIV infection, who received ART in a scheme consisting of Tenofovir/Emtricitabine+Lopinavir/Ritonavir, were enrolled in this study. The serum levels of FGF21, inflammatory parameters (IL-6 and IL-1β), glucose, cholesterol, triglycerides, and insulin were determined at baseline and after 36 weeks of treatment. The homeostatic model assessment for insulin resistance (HOMA-IR) and the atherogenic risk factor were also calculated. Results: After 36 weeks, serum FGF21 levels decreased significantly (p=0.011), whereas IL-6 levels (r=0.821, p=0.0001) and the CD4+ T cell count (r=0.446, p=0.048), showed a positive correlation with the decrease in FGF21 levels. There was an increase in total cholesterol (r=-0.483, p=0.031), LDL (r=-0.496, p=0.026), VLDL (r=-0.320, p=0.045), and the atherogenic index factor (r=-0.539, p=0.014), these values showed a negative correlation with FGF21 levels. Conclusion: The decrease of serum FGF21 levels due to ART is associated with the alteration in lipid profile and an increased risk for cardiovascular diseases. These variations are predictors of inflammatory status in HIV patients using antiretroviral therapy.
Keywords: Antiretroviral therapy